Designing a Cashier Website for Warkop Disini Aja Using the Laravel Framework with UAT Testing and Usability Testing Checklist - Rahman, Taufik; Rahmanaufal, Fatta Rahmanaufal (Computer Science and Information Technology, 2025)
Advances in information technology have a significant influence on various sectors, including Micro, Small, and Medium Enterprises (MSMEs). However, most MSMEs still have not adopted digital systems in their operational activities. One example is Warkop Diini Aja, which until now still applies manual recording to the cashier transaction process. The use of the conventional system poses various obstacles, such as delays in making reports, potential for recording errors, and difficulties in monitoring sales history. Based on these problems, this research aims to design a web-based cashier system that is able to replace manual methods to be more efficient and structured. System development is carried out using the Laravel framework with a waterfall software development model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. Research data was obtained through direct observation of operational processes, interviews with business owners, and literature review to strengthen the theoretical basis. The developed system has two main roles, namely admin and cashier, which are equipped with menu management features, sales transactions, export reports in digital format, and transaction history monitoring. Based on the results of the User Acceptance Testing (UAT) test, all system functions are declared to run according to user needs. In addition, the results of the Usability testing Checklist show a user satisfaction rate of 95%, which is classified as very feasible. Thus, this website-based cashier system has been proven to be able to improve operational efficiency, make it easier to record transactions, strengthen financial report transparency, and support more modern and digital business management.